English Learning Materials for Grade XI Students of Multimedia Study Program (RETAIN, 2020)
English is one of the subjects that must be taught in school or university. In high school, the syllabus for senior high school and vocational school is the same based on the 2013 curriculum. This is not in line with the theory of English for Specific Purposes where vocational high school has different majors and requires specific English material that is appropriate for each majors. Therefore, designing English material is needed to fulfill the needs, interests and demands of students, especially for multimedia students. This study was conducted to find out what material should be included for Multimedia major and to describe how English material for multimedia majors was developed. This research was used the Research and Development method adapting the procedure suggested by Gall and Borg (2003). The results of this study showed that the materials that must be included for multimedia major are materials related to technology and multimedia. Then, activities that must be provided are reading and speaking in English; audio/video related to multimedia; and discussion for teaching technique. Based on the teacher's opinions on the developed material, several components such as language, content, and graphics as well as the material categorized as appropriate materials since it based on the multimedia students' needs.